Voluntary disclosure and firm value: Evidence from Indonesia - Hadi Mahmudah; Andi Ina Yustina; Christine Novita Dewi; Bambang Sutopo (Cogent Business & Management)
Climate change carries risks that need to be mitigated by all parties, including companies because it affects company value. Many studies find that voluntary disclosure positively affects firm value in developing countries. This study aims to examine the effect of voluntary disclosure (CSR and carbon disclosure on firm value) in the developing country of Indonesia. Researchers suspect that voluntary disclosure practice in developing countries is still low, so that investors respond negatively. To test the hypothesis using regression with a total of 72 observations from the energy sector companies. The results of the study show that voluntary disclosure has a negative effect on firm value. The level of voluntary disclosure in Indonesia is still low, just complying with government regulations, and it is still considered a cost that affects the firm’s value. The implication of this research is to encourage the government to immediately make regulations and concrete steps to mitigate the impact of climate change.